Scaredy pug - May, Kyla (2021)
Baron von Bubbles (Bub) the pug, Duchess the cat, and their human, Bella, are going to the countryside to visit Bella's grandmother for a few days, where they expect to have fun building forts and dressing up in the attic--but the attic seems to be haunted, and neither Bub nor Duchess can summon up the courage to face the ghost.
Keywords: Pug -- Juvenile fiction; Cats -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Haunted houses -- Juvenile fiction; Fear -- Juvenile fiction; Humorous stories; Pug -- Fiction; Dogs -- Fiction; Cats -- Fiction; Human-animal relationships -- Fiction; Haunted houses -- Fiction; Fear -- Fiction; Diaries -- Fiction; Humorous stories; Humorous fiction